2022
DOI: 10.33828/sei.v33.i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Modelling as a Tool to Improve Second Language Learners’ Descriptions of Non-Spontaneous Chemistry Concepts

Abstract: This study investigated how modelling in chemistry affect second language learners’ descriptions of polymeric concepts. The aim was to investigate how chemistry discussions mediated by representations, contribute to second language students’ development in the language of chemistry. The study took place in three multilingual upper secondary classes. Participating students were (n=16) second language learners and (n=14) first language learners. There were in total eight different first languages represented. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…In Sweden, it is common for chemistry education at the upper secondary level to be conducted in multilingual classroom settings. This study is part of a context in which modelling-based teaching in a multilingual context is investigated to improve second language learners' descriptions of chemistry concepts; for more information, see Widing et al (2022). Data were collected from eight multilingual groups.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Sweden, it is common for chemistry education at the upper secondary level to be conducted in multilingual classroom settings. This study is part of a context in which modelling-based teaching in a multilingual context is investigated to improve second language learners' descriptions of chemistry concepts; for more information, see Widing et al (2022). Data were collected from eight multilingual groups.…”
Section: Methodsmentioning
confidence: 99%
“…Modelling-based teaching aims to contribute to students' active involvement in their learning process and enables students to discuss chemistry when creating, questioning, and evaluating representations. Other studies have shown that when students fail to express their chemical understandings verbally, representation can support argumentation (Gilbert and Justi, 2016;Widing et al, 2022).…”
Section: Models and Modelling In Chemistry Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…With a sense of how science education researchers conceptualize language, we now turn to patterns between researchers’ language conceptualizations and the science practice(s) under study. As shown in Table 2, most of the studies examined multilingual students’ experiences with argumentation (e.g., Alvarez et al, 2023; González-Howard et al, 2017), modeling (e.g., Widing et al, 2022; Pearce et al, 2020; Ryoo et al, 2018), and/or explanation (e.g., Kang et al, 2017; Rutt & Chang-Bacon, 2023; Ryoo & Bedell, 2019), in that order of frequency.…”
Section: Findings From the Literature Synthesismentioning
confidence: 99%